New insights into the analgesic properties of the XCL1/XCR1 and XCL1/ITGA9 axes modulation under neuropathic pain conditions - evidence from animal studies - Ciechanowska, Agata; Rojewska, Ewelina; Piotrowska, Anna; Barut, Justyna; Pawlik, Katarzyna; Ciapała, Katarzyna; Kreiner, Grzegorz; Mika, Joanna (Frontiers in Immunology, 2022)
Recent studies have indicated the involvement of chemokine-C-motif ligand 1 (XCL1) in nociceptive transmission; however, the participation of its two receptors, canonical chemokine-C-motif receptor 1 (XCR1) and integrin alpha-9 (ITGA9), recently recognized as a second receptor, has not been clarified to date. The aim was to explore by which of these receptors XCL1 reveals its pronociceptive properties and how the XCL1-XCR1 and XCL1-ITGA9 axes blockade/neutralization influence on pain-related behavior and opioid analgesia in the model of neuropathic pain. In our studies we used Albino Swiss mice which were exposed to the unilateral sciatic nerve chronic constriction injury (CCI) as a neuropathic pain model. Animals received single intrathecal (i.t.) injection of XCL1, XCL1 neutralizing antibodies, antagonist of XCR1 (vMIP-II) and neutralizing antibodies of ITGA9 (YA4), using lumbar puncture technique. Additionally we performed i.t. co-administration of abovementioned neutralizing antibodies and antagonists with single dose of morphine/buprenorphine. To assess pain-related behavior the von Frey and cold plate tests were used. To measure mRNA and protein level the RT-qPCR and Western Blot/Elisa/immunofluorescence techniques were performed, respectively. Statistical analysis was conducted using ANOVA with a Bonferroni correction. Presented studies have shown time-dependent upregulation of the mRNA and/or protein expression of XCL1 in the spinal cord after nerve injury as measured on day 1, 4, 7, 14, and 35. Our immunofluorescence study showed that XCL1 is released by astroglial cells located in the spinal cord, despite the neural localization of its receptors. Our results also provided the first evidence that the blockade/neutralization of both receptors, XCR1 and ITGA9, reversed hypersensitivity after intrathecal XCL1 administration in naive mice; however, neutralization of ITGA9 was more effective. In addition, the results proved that the XCL1 neutralizing antibody and, similarly, the blockade of XCR1 and neutralization of ITGA9 diminished thermal and mechanical hypersensitivity in nerve injury-exposed mice after 7 days. Additionally, neutralization of XCL1 improves morphine analgesia. Moreover, blockade of XCR1 positively influences buprenorphine effectiveness, and neutralization of ITGA9 enhances not only buprenorphine but also morphine analgesia. Therefore, blockade of the XCL1-ITGA9 interaction may serve as an innovative strategy for the polypharmacotherapy of neuropathic pain in combination with opioids.